THE NEXUS BETWEEN LEADERSHIP STYLES, ORGANIZATIONAL CULTURE, AND FINANCIAL OUTCOMES - safii, Nur Muhamad (Journal of Management Economic and Financial, 2024)
Leadership and culture organization is two factor strategic that influences performance finance company . However , the findings empirical related connection both of them Still diverse , especially in Indonesian context . Research This aim For analyze influence style leadership to culture organization and results finance , as well as test role mediation culture organization in the company medium and large enterprises in Indonesia. Research This use approach quantitative explanatory with method survey . Primary data was collected through questionnaire to 220 managers middle and upper class , while secondary data originate from report finance company . Analysis done with Structural Equation Modeling (SEM) using SmartPLS . Research results show that (1) style leadership influential positive significant to culture organization ; (2) style leadership influential direct to results finance , although its influence relatively small ; (3) culture organization influential significant to results finance ; and (4) culture organization mediate connection between style leadership and results finance . Research This confirm that leadership transformational play a role important in form culture adaptive organization , which in turn increase profitability company . Implications study This emphasize importance investment company in development leadership and transformation culture organization as an improvement strategy Power competitiveness and sustainability business in Indonesia.